Silicon-carbon composite fiber
Silicon-carbon composite fibers address the swelling issues of silicon anodes in lithium-ion batteries by forming a stable network structure, enhancing Coulomb efficiency and specific delithium capacity.
Patent Information
- Application Number
- JP2024555889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-21
- Filing Date
- 2023-03-21
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium-ion batteries face challenges with silicon anode materials due to significant swelling during lithiumization, leading to internal structure breakdown and loss of electrical connectivity.
The development of silicon-carbon composite fibers with a network structure of intertwined silicon and carbon phases, where the silicon phase is nanocrystalline or amorphous and the carbon phase is amorphous or crystalline, to form a stable and efficient anode material.
The silicon-carbon composite fibers improve the Coulomb efficiency and specific delithium capacity of lithium-ion batteries, reducing the risk of structural damage and maintaining electrical connectivity over cycles.
Smart Images

Figure 2025510676000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 63 / 269,652, filed March 21, 2022, which is incorporated by reference in its entirety.
[0002] The present disclosure relates to silicon-carbon composite fibers and methods of making and using same. [Background technology]
[0003] Lithium-ion batteries have seen rapid adoption over the past decade and are now the power source of choice for providing portable power to electronic devices, cordless devices and vehicles. As technology becomes more and more dependent on lithium-ion battery power, the lithium-ion battery industry has worked to expand the capabilities of the cells to provide maximum versatility to end users.
[0004] Graphite is commonly used in lithium-ion batteries because it can remain stable and perform its function for hundreds of cycles with little capacity loss. Silicon has great potential as an anode material because of its very high capacity (4000mAh / g) versus the current industry standard of graphite (372mAh / g). However, silicon has a limitation in that it swells by 350% upon lithiation. This swelling causes severe destruction of the cell's internal structure, damaging the cell's components, and the anode itself shatters into pieces, ultimately losing electrical connectivity, resulting in rapid capacity loss. Thus, there is a continuing need for improved silicon-containing anode materials and methods for preparing such silicon-containing anode materials. [Brief description of the drawings]
[0005] Various embodiments of the present disclosure will become more fully understood from the following detailed description and the accompanying drawings, in which like reference numbers may indicate identical or functionally similar elements. Embodiments will now be described in detail with reference to the accompanying drawings, in which: [Figure 1] FIG. 1 is a graph summarizing the results of Example 1. [Diagram 2] FIG. 2 is a graph summarizing the results of Example 1. [Diagram 3] FIG. 3 is a graph summarizing the results of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The following disclosure provides many different embodiments or examples. To simplify the disclosure, specific examples of components and arrangements are described below. Of course, these are merely illustrative and are not intended to be limiting. Furthermore, the disclosure may repeat reference numerals and / or letters in various examples. This repetition is for simplicity and clarity, and does not in itself dictate a relationship between the various embodiments and / or configurations described.
[0007] Composite Fiber The present invention provides silicon-carbon composite fibers having a silicon phase ("Si phase") and a carbon phase ("C phase"). The Si phase and C phase form an entangled network in the fiber, with each phase interconnected and continuous throughout the fiber. The Si phase has nanocrystalline or amorphous elemental silicon. The Si phase is present in the fiber in a range of from greater than 0 wt% to less than 100 wt%. The C phase has amorphous or crystalline carbon and is present in the fiber in a range of from greater than 0 wt% to less than 100 wt%. In some embodiments, the sum of the Si phase and the C phase is in the range of from 50 wt% to 100 wt%. In some embodiments, the C phase comprises at least 30 wt% of the fiber and / or the Si phase comprises at least 20 wt% of the fiber.
[0008] In one or more embodiments, the composite fibers may also include amorphous or crystalline silicon oxide, SiOx (x≦2). The composite fibers may also include other impurities such as aluminum (Al), magnesium (Mg), chlorine (Cl), sodium (Na), nitrogen (N), carbon oxides (COx) (x≦2), and / or hydrocarbon chains. In some embodiments, the composite fibers have 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, or 1 wt% or less Al. In some embodiments, the composite fibers have 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, or 1 wt% or less Mg. In some embodiments, the composite fibers have 40 wt% or less, 35 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, or 5 wt% or less of amorphous or crystalline silicon oxide, SiOx (x≦2).
[0009] In one or more embodiments, the bicomponent fibers of the present disclosure have a fiber length of greater than 0 to 100 m. 2 / g, 0.1-45m 2 / g, 0.1-10m 2 / g, or 0.1 to 6m 2 / g BET specific surface area ("SSA").
[0010] In one or more embodiments, the bicomponent fiber has a thickness of greater than 0 to 0.3 cm 3 / g, 0.01~0.3cm 3 / g, over 0~0.05cm 3 / g, 0.01~0.03cm 3 / g, over 0~0.1cm 3 / g, 0.02~0.06cm 3 / g, or 0.05 to 0.25 cm 3 / g pore volume.
[0011] In one or more embodiments, the composite fibers have an average pore size of 5 to 80 nm, 15 to 55 nm, 20 to 35 nm, or 15 to 40 nm.
[0012] In one or more embodiments, the bicomponent fibers have an average diameter of 0.1 to 20 microns, 0.1 to 10 microns, 0.5 to 6 microns, 1 to 8 microns, or 2 to 5 microns.
[0013] In one or more embodiments, the bicomponent fibers have an aspect ratio of fiber length to diameter of at least 3, at least 5, or at least 10.
[0014] The nanocrystalline silicon (elemental silicon) of the Si phase may have crystallites with an average size of 10-100 nm, 15-50 nm, 20-45 nm, 20-50 nm, or 20-40 nm. In some embodiments, the Si phase has at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 75 wt%, at least 80 wt%, 75-90 wt%, or at least 90 wt% nanocrystalline silicon, based on the total weight of the Si phase. In some embodiments, the Si phase has up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous or crystalline silicon oxide (SiO x (x≦2). In some embodiments, the Si phase consists of nanocrystalline silicon, amorphous silicon, and amorphous or crystalline silicon oxide.
[0015] In some embodiments, the Si phase consists of amorphous silicon and crystalline silicon, or consists of crystalline silicon. In such embodiments, a silica phase may be present, and the silica phase consists of amorphous and / or crystalline silicon oxide. The silica phase may be continuous or discontinuous in the composite fiber. For example, the silica phase may form islands in the Si phase and / or C phase. In some embodiments, the weight ratio of the Si phase to the silica phase in the composite fiber is 1:1 to 30:1, 1:1 to 20:1, 2:1 to 10:1, or 5:1 to 10:1. In some embodiments, the silica phase is primarily amorphous silica, and the weight ratio of amorphous silica to crystalline silica is greater than 1:1 to 500:1, 2:1 to 200:1, 10:1 to 100:1, or 50:1 to 100:1.
[0016] Crystalline silicon is formed from silicon crystallites. Without being bound by theory, it is believed that a silicon crystallite size of at least 10 nm enhances the first cycle coulombic efficiency (FCE) of a half-cell containing the composite fiber. FCE measures the amount of capacity irreversibly lost during the first cycle of a battery. It is important to minimize this loss, since the lost capacity (i.e., the consumed lithium ions) is retained as dead weight in the battery for the life of the battery. This loss is believed to occur primarily through the formation of a solid electrolyte interface (SEI) on the surface of the active material that traps lithium inside the silicon particles. By increasing the size of the silicon crystallites, the percentage of lithium ions consumed during SEI formation on the silicon crystallite surface decreases because the specific surface area of the material decreases with increasing crystallite size.
[0017] The C phase may have carbon crystallites with sizes ranging from 1 to 100 nm, 15 to 50 nm, 1 to 50 nm, or 5 to 20 nm. In some embodiments, the C phase has at least 50 wt%, at least 60 wt%, at least 70 wt%, or at least 80 wt% crystalline carbon, based on the total weight of the C phase. In other embodiments, the C phase has up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% crystalline carbon. In some embodiments, the C phase has up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous carbon. In other embodiments, the C phase has at least 50 wt%, at least 60 wt%, at least 70 wt%, or at least 80 wt% amorphous carbon. In some embodiments, the C phase consists of crystalline carbon and amorphous carbon.
[0018] In one or more embodiments, based on the weight of each phase, one of the Si phase or the C phase has a crystalline content greater than 50 wt% and the other of the Si phase or the C phase has a crystalline content less than 50 wt%. In some embodiments, the crystalline content of one of the Si phase or the C phase is greater than 60 wt% and the crystalline content of the other of the Si phase or the C phase is less than 40 wt%. In some embodiments, the crystalline content of one of the Si phase and the C phase is greater than 70 wt% and the crystalline content of the other of the Si phase and the C phase is less than 30 wt%.
[0019] Carbon precursor fiber In some embodiments, the composite fibers are formed by infiltrating the carbon structure with silicon. For example, the composite fibers can be formed by first producing porous carbon fibers and then infiltrating the pore structure with silicon. Silicon infiltration can be performed by a chemical vapor deposition (CVD) process using silicon precursor gases such as silane or trichlorosilane. The production of porous carbon fibers can include multiple steps. For example, synthetic polymer fibers can be produced first with polymers such as polyacrylonitrile (PAN), pitch, rayon, resin, etc. Then, carbon fibers can be produced by pyrolyzing the synthetic polymer. To make the carbon fibers porous, the carbon fibers can be treated by activation or chemical exfoliation. In the activation method, the carbon fibers are heat treated (e.g., 700°C to 1000°C) in an oxidizing atmosphere to form the porous structure of the carbon fibers. In the chemical exfoliation method, the carbon fibers can be treated with a release agent such as an acid and an electric charge can be applied to the fibers. Alternatively, a polymer blend, for example, a mixture of PAN and polymethyl methacrylate (PMMA), can be fiberized to form polymer fibers, which are then oxidized to cause phase separation. The PMMA is then removed by pyrolysis, leaving behind the porous carbon fibers.
[0020] In some embodiments, the porous carbon fibers before being infiltrated with silicon have at least 50 wt%, at least 60 wt%, at least 70 wt%, or at least 80 wt% crystalline carbon. The porous carbon fibers may have up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous carbon. The porous carbon fibers may have up to 15 wt%, up to 10 wt%, or up to 5 wt% impurities (components other than crystalline or amorphous carbon).
[0021] Porous silicon fiber template (PSFT) In some embodiments, the composite fiber is formed by infiltrating carbon into a silicon structure. For example, the composite fiber may be formed by first producing a porous silicon fiber template (PSFT) with metal silicon and then infiltrating carbon into the pores. To produce the PSFT, a SiO2-containing fiber, i.e., a precursor fiber, is first produced. The precursor fiber can be a silica fiber produced by a sol-gel fiberization method or by acid leaching an oxidized glass fiber.
[0022] The precursor fibers are reduced to PSFT with metallic silicon, for example by magnesiothermic reduction. The PSFT is then infiltrated with carbon, for example through a chemical vapor deposition (CVD) process using a carbon source such as acetylene, or using other deposition processes such as physical vapor deposition, sputtering, atomic layer deposition, or alternatively, the porous fibers are first infiltrated with a hydrocarbon polymer (e.g., a resin, polyvinyl acetate (PVA)) and the polymer is converted to carbon by pyrolysis.
[0023] In one or more embodiments, the silicon crystallite size in PSFT can be controlled by the magnesiothermic reduction conditions. In particular, it has been found that larger temperature increases and / or longer exposure to such temperatures tend to result in the formation of larger silicon crystallites. The thermal effect ΔT is characterized by the calculated temperature increase due to the exothermic magnesiothermic reduction reaction (i.e., an increase above the calcination temperature used to initiate the reaction, e.g., about 550-600° C.). The magnesiothermic reduction reaction is as follows: TIFF2025510676000002.tif11159
[0024] The maximum temperature rise (ΔT) due to this reaction can be estimated as follows: TIFF2025510676000003.tif20159 where ΔH is the enthalpy per mole of reaction, M Mg is the molar mass of Mg, m Mg、 m Si , m MgO , m mod are the masses of Mg, Si, MgO, and the moderator, respectively, and C p、Si , C p、MgO , C p , mod are the specific heat capacities of Si, MgO, and the moderator, respectively.
[0025] In some embodiments, ΔT may be maintained in the range of about 300° C. to about 900° C., or about 300° C. to about 700° C. ΔT may be controlled, for example, by varying the amount of moderator used in the reaction. In general, increasing the amount of moderator decreases ΔT because the moderator constitutes a thermal mass that absorbs the heat of reaction. Moderators may include, but are not limited to, sodium chloride, alumina, alumina silicate, zirconia, zirconia silicate, magnesia, carbon, silicon carbide, silicon nitride, or any material having a melting point of at least 800° C. The exposure time of PSFT to ΔT may be very short (e.g., nearly instantaneous). In some embodiments, an insulating crucible, such as an alumina crucible, may extend the effect of ΔT, thereby forming larger crystallites at a relatively low ΔT (e.g., about 200° C. to about 600° C.).
[0026] High ΔT or prolonged exposure to such temperatures can result in the formation of many by-products, such as forsterite, ringwoodite, crystalline silica, spinel, enstatite, and / or pyroxene. In some embodiments, the PSFT may be subjected to a wash, such as an acid wash, to remove one or more of these by-products. In some embodiments, the PSFT before or after washing may contain up to 10 wt%, up to 5 wt%, up to 3 wt%, up to 2 wt%, or up to 1 wt% of total by-products. In some embodiments, forsterite is present in the washed or unwashed PSFT in an amount of up to 5 wt%, up to 3 wt%, up to 2 wt%, less than 2 wt%, or less than 1 wt%. In some embodiments, ringwoodite is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, or less than 1 wt%. In some embodiments, enstatite is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, spinel is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, crystalline silica is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, pyroxene is present in the washed or unwashed PSFT in an amount of up to 3 wt%, up to 2 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some embodiments, ΔT is maintained below 700° C., below 600° C., or below 500° C. to minimize the formation of such by-products.
[0027] In some embodiments, the maximum reaction temperature observed during the magnesiothermic reduction of the silica fibers (typically for a fraction of a second) is 1500° C., 1400° C., 1300° C., 1200° C., 1100° C., 1000° C., 900° C., 800° C., 700° C., or 600° C. In some embodiments, the maximum reaction temperature is at least 300° C., 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or 1400° C. In some embodiments, the maximum reaction temperature can be within any logical combination of the foregoing upper and lower limits.
[0028] The PSFT with metal silicon acts as a template matrix for incorporating carbon to form composite fibers. Metal silicon-containing fibers also have average pore sizes ranging from 5 to 80 nm, 0.2 to 0.9 cm. 3 / g range of pore volume, and 50 to 350 m 2 / g. The PSFT may have a crystalline silicon content (Si%) of 50-100 wt%, at least 75 wt%, 75-90 wt%, or at least 90 wt%, and a silicon crystallite size of 10-100 nm, 15-50 nm, 20-50 nm, 20-45 nm, or 20-40 nm.
[0029] In some embodiments, PSFT is a composite of crystalline silicon in the range of 50-100 wt % and amorphous silicon oxide (SiO x ), which is determined by Rietveld analysis. The amorphous silicon oxide in PSFT can be stoichiometric (SiO2) or nonstoichiometric (SiO x, x<2). In some embodiments, the PSFT before carbon infiltration has at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 75 wt%, 75-90 wt%, at least 80 wt%, or at least 90 wt% crystalline silicon (nanocrystalline silicon). The PSFT may have up to 50 wt%, up to 40 wt%, up to 30 wt%, up to 20 wt%, or up to 10 wt% amorphous or crystalline silicon oxide. The PSFT may have up to 15 wt%, up to 10 wt%, or up to 5 wt% impurities (components other than silicon or silicon oxide).
[0030] Examples of PSFT material properties are summarized in Table 1 below. Material properties can be controlled by reduction recipe design, firing temperature program, post heat treatment, loading ratio, and / or moderator particle size. For example, varying the moderator particle size changes the batch stacking density and the spatial division between reactants. Larger moderator particles tend to have larger crystallite sizes. In some embodiments, larger crystallite sizes may be achieved by a two-stage firing process, where a first firing is performed in the presence of moderator to achieve a crystallite size of about 6-12 nm, and a second firing with reduced (or no) moderator increases the crystallite size to about 20-100 nm. Between the first and second firings, the fired batch is sieved to remove moderator remaining from the first firing and / or washed to remove magnesium oxide (MgO). With respect to the loading ratio, a higher loading relative to the size of the heating vessel (e.g., crucible, conveyor belt, rotary kiln, etc.) typically results in a larger crystallite size because the heating vessel acts as a moderator. That is, in a continuous process, a higher feeding rate to the conveyor belt may result in a larger crystallite size, and in a batch process, a higher loading amount in the batch may result in a larger crystallite size. In some embodiments, the weight ratio of moderator (e.g., sodium chloride and / or alumina) to magnesium is at most 15, at most 12, at most 10, or at most 7.
[0031] [Table 1]
[0032] In one or more embodiments, the PSFT is infiltrated with carbon to form a composite fiber. In such embodiments, the Si-C composite fiber may have a carbon content of 20-70 wt%, 20-45 wt%, 32-50 wt%, or 30-50 wt%, an FCE of at least 78%, and a first cycle specific delithiation capacity (1SDC) in a half-cell test of at least 1300 mAh / g or at least 1800 mAh / g.
[0033] In one or more embodiments, the majority elements in the composite fibers are Si, C, and oxygen (O), e.g., these elements comprise at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 99 wt%, or at least 99.5 wt% of the composite fibers.
[0034] In some embodiments, the composite fiber has a value of at least 77, at least 78, at least 79, or at least 80 for Equation 1 below, where X is the average silicon crystallite size (nm) in the Si phase and Y is the weight percent of the C phase based on the total weight of the composite fiber. 85.634*X / (X+0.0824*(62.79-Y)) Equation 1
[0035] In some embodiments, the composite fiber has a value of Equation 2 below of at least 1200, at least 1300, at least 1400, at least 1500, at least 1800, or at least 2000, where Y is the weight percent of the C phase based on the total weight of the composite fiber, and Z is the weight percent of elemental silicon in the Si phase. 31.486*(100-Y)*Z / 100 Equation 2
[0036] In some embodiments, the composite fiber includes a Si phase having at least 90 wt% crystalline silicon with an average crystallite size of 20-40 nm and a C phase that constitutes 20-45 wt% of the composite fiber. Anodes including the composite fiber may provide a 1SDC of greater than 1800 mAh / g and an FCE of greater than 78%.
[0037] In some embodiments, the composite fibers include a Si phase having 75-90 wt% crystalline silicon with an average crystal size of 20-45 nm, and a C phase that constitutes 32-50 wt% of the composite fibers. Anodes including the composite fibers may provide 1SDC greater than 1300 mAh / g, FCE greater than 78%, and 10th cycle coulombic efficiency (10CE) greater than 98.7%.
[0038] According to the embodiments of the present disclosure, the FCE is improved by forming composite fibers of entangled Si-C domains. The specific capacity is expected to decrease to a minimum at 100% carbon (about 372 mAh / g when the carbon is pure graphite, and even lower when the carbon is carbon black). Therefore, it is important to balance the FCE and capacity by properly adjusting the amount of carbon infiltration, especially in full cell or battery design.
[0039] The amount of carbon that can be infiltrated into PSFT is generally limited by the pore volume of the PSFT, i.e., the void space accessible to carbon: the larger the pore volume, the more carbon can be infiltrated, thus resulting in a higher carbon content.
[0040] When carbon or silicon infiltrates the PSFT or carbon fibers, the total volume of the formed Si-C composites remains unchanged relative to the original PSFT or carbon fiber template. Meanwhile, the FCE is significantly improved, increasing the charge / discharge volumetric capacity of the single fiber. Therefore, the composite Si-C fibers can offer superior properties compared to simple mixtures of Si fibers and carbon materials (e.g., carbon black and graphite).
[0041] Without being bound by theory, it is believed that this is at least in part due to the interconnected carbon network in the fiber, which enhances the transport and diffusion rate of electrons and lithium ions. Electrons and lithium ions diffuse faster in carbon than in silicon. The interconnected carbon network in the composite fiber facilitates the transport of electrons and lithium ions from the outer surface of the composite fiber to the interior of the composite fiber, or from the interior of the composite fiber to the outer surface of the composite fiber. Thus, the number of electrons and lithium ions, and their transport rate, increases with the carbon content in the fiber.
[0042] The improved diffusion rate also shortens the exposure time of the tensile stress buildup on the Si domain surface during the delithiation process, which helps to prevent cracking of the silicon domain.The improved diffusion rate also shortens the exposure time of the tensile stress buildup on the fiber surface during the delithiation process, which helps to avoid cracking of the fiber surface.
[0043] In some embodiments, the composite fibers may include lithium, where the lithium and at least a portion of the silicon from the Si phase are Li x In some embodiments, the lithium-containing composite fiber further comprises Li2SiO 3を In some embodiments, the lithium-containing composite fibers are prepared by preparing a nanoporous fibrous structure of either silicon or carbon, then infiltrating the structure with the other of carbon or silicon, and then reacting the infiltrated structure with a lithium source to produce Li x In other embodiments, lithium-containing composite fibers can be formed by creating a nanoporous fibrous structure of silicon and then reacting the structure with a lithium source to form a Li x In yet another embodiment, the lithium-containing composite may be formed by incorporating lithium into a Si-C composite fiber to form a Li x It may be formed by forming a Si alloy.
[0044] Working Example: EXAMPLES
[0045] Example 1 Batches of PSFT were prepared using the thermal magnesia reduction method under various conditions and then each was infiltrated with carbon. The compositions of the resulting fibers were as shown in Tables 2 and 3 below. Half cells were prepared for several batches of fibers and the FCE, 5 cycle coulombic efficiency (5CE), 1SDC, and 10th cycle coulombic efficiency (10CE) were measured. The results are summarized in Table 4 below.
[0046] [Table 2] TIFF2025510676000006.tif200159TIFF2025510676000007.tif83159
[0047] [Table 3] TIFF2025510676000009.tif200159TIFF2025510676000010.tif174159
[0048] [Table 4] TIFF2025510676000012.tif200159TIFF2025510676000013.tif76159
[0049] Blank cells in Tables 2-4 indicate properties that were not measured or could not be detected.
[0050] As shown above, by maintaining the desired silicon content, crystallite size, and carbon content, Examples 1-27 each achieved an FCE of at least 78% and an 1SDC of at least 1300 mAh / g. In contrast, Comparative Examples 1 and 2 had very large crystallites and exhibited FCEs of 75.8% and 62.1%, and 1SDCs of 1162 and 1057 mAh / g, respectively. Comparative Example 3 had low silicon content and poor 1SDC. Comparative Examples 4 and 5 had very high carbon content and poor 1SDC. Comparative Examples 6 and 7 had good 1SDC but poor FCE due to low carbon content. Comparative Examples 8-18 had small crystallites and / or high carbon content, resulting in poor 1SDC and / or FCE. Comparative Examples 19-32 each had silicon crystallite sizes less than 10 nm and only achieved a maximum FCE of 65.5%. Figure 1 shows the effect of silicon crystallite size on 1SDC. Figure 2 shows the effect of silicon content and silicon crystallite size in the composite fiber on 10CE. EXAMPLES
[0051] Example 2: Effect of heat on crystallite size Table 5 below summarizes the reduction conditions for PSFT selected from Table 2 above. To form PSFT, a mixture of silica fiber, Mg, and moderator (sodium chloride, alumina beads, and / or plate-like alumina) was charged into a reactor. Specifically, Comparative Examples 1-3 used an alumina crucible, Comparative Examples 4, 5, 10-20, 26-30 and Examples 6, 7, 9, 11, 22, 26 used a metal crucible, and the remaining Examples used a rotary kiln. The reaction was carried out in an argon atmosphere, and the fibers were cleaned before analysis (analysis results are in Table 2). As shown, by controlling the reaction conditions, such as the ratio of moderator to magnesium, the crystallite size can be adjusted to fall within the ranges disclosed herein. Selected Examples are plotted in Figure 3 to show the effect of ΔT on silicon crystallite size.
[0052] [Table 5] TIFF2025510676000015.tif200159TIFF2025510676000016.tif200159TIFF2025510676000017.tif146159
[0053] While various embodiments have been shown and described, it will be understood that the disclosure is not limited to such embodiments, but includes all modifications and variations apparent to those skilled in the art. It is therefore to be understood that the disclosure is not intended to be limited to the particular forms disclosed, but is intended to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the disclosure as defined by the appended claims.
Claims
1. A composite fiber, a porous silicon phase having elemental silicon; A porous carbon phase having elemental carbon. having the silicon phase and the carbon phase form an entangled network structure in the composite fiber, whereby each of the silicon phase and the carbon phase is interconnected and continuous throughout the composite fiber; the silicon phase having at least 75 weight percent elemental silicon in the form of silicon crystallites having an average size of 15 to 50 nm; the carbon phase comprises 20 to 60 weight percent of the composite fiber; The silicon phase and the carbon phase together comprise at least 50 weight percent of the composite fiber. Composite fiber.
2. The composite fiber according to claim 1, wherein the composite fiber has a length of 0.1 to 45 m. 2 / g BET specific surface area and 0 to 0.25 cm 3 / g of pore volume.
3. 10. The composite fiber of claim 1, wherein the composite fiber has an average pore size of 5 to 80 nm.
4. 10. The composite fiber of claim 1, wherein the composite fiber has an aspect ratio of fiber length to diameter of at least 3.
5. 10. The composite fiber of claim 1, wherein said silicon phase and said carbon phase collectively comprise at least 90 weight percent of said composite fiber.
6. 6. The composite fiber of claim 5, wherein the silicon phase has at least 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 40 nm, and the carbon phase comprises 20 to 45 weight percent of the composite fiber.
7. 6. The composite fiber of claim 5, wherein the silicon phase has 75 to 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 45 nm, and the carbon phase comprises 32 to 50 weight percent of the composite fiber.
8. A method for producing the composite fiber according to claim 1, comprising the steps of: forming a porous fibrous template having one of carbon or silicon, the porous fibrous template having one of the silicon phase or the carbon phase; forming an infiltrated phase by infiltrating the porous fibrous template with the other of carbon or silicon, the infiltrated phase having the other of the silicon phase or the carbon phase; The method according to claim 1,
9. The method of claim 8 , wherein the porous fibrous template consists essentially of carbon.
10. The method of claim 8 , wherein the porous fibrous template consists essentially of silicon.
11. The method of claim 8, wherein the average pore size of the infiltrating phase is 0.1 to 5 nm smaller than the average pore size of the porous fibrous template.
12. The method of claim 11 , wherein infiltrating the porous fibrous template comprises chemical vapor deposition, physical vapor deposition, sputtering, atomic layer deposition, or pyrolysis.
13. 12. The method of claim 11, wherein the porous fibrous template comprises silicon, and the step of forming the porous fibrous template comprises: heating the silica precursor fibers to a temperature of about 550° C. to about 600° C. in the presence of magnesium and a moderator, said moderator being present in an amount sufficient to reach a maximum reaction temperature of at least 300° C. having the weight ratio of said moderator to said magnesium is less than 15; method.
14. 14. The method of claim 13, wherein the moderator comprises sodium chloride and the maximum temperature is maintained below 900°C.
15. 10. The method of claim 8, further comprising reacting the composite fiber with a lithium source to form Li x The method includes forming a Si-alloy, wherein x is from 0 to 4.
16. An electrode active material comprising the composite fiber according to claim 1.
17. 17. An electrode comprising the electrode active material of claim 16, the electrode having a first coulombic efficiency of at least 78% and a first cycle delithiation capacity of at least 1300 mAh / g.
18. 18. The electrode of claim 17, wherein the silicon phase has at least 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 40 nm, and the carbon phase comprises 20 to 45 weight percent of the composite fiber; The electrode has a first cycle specific delithiation capacity of at least 1800 mAh / g.
19. 18. The electrode of claim 17, wherein the silicon phase has 75 to 90 weight percent elemental silicon, the silicon crystallites have an average size of 20 to 45 nm, and the carbon phase comprises 32 to 50 weight percent of the composite fiber; The electrode has a 10th cycle coulombic efficiency of greater than 98.7%.
20. A battery comprising the electrode of claim 16.
Citation Information
Patent Citations
Novel material having highly durable lithium insertion and method for manufacturing the same
JP2018534720A
Porous silicon-containing composite, carbon composite using the same, electrode, lithium battery, and electronic element including the same
JP2020066574A
Carbon aerogel-based electrode materials and methods of manufacture thereof
US20200269207A1